(untitled) (Research, Society and Development, 2020)
The goal of this work was to assess the awareness level of vegetable producers about the use of pesticides in Goiatuba and Morrinhos, South of Goiás. The survey was carried out on 20 properties using a questionnaire. It was found that the production of vegetables is carried out in a polyculture system, in small areas, and with family labor. However, the scarcity of technical assistance is a bottleneck hindering the optimization of the production process. Most producers are male and have incomplete elementary education. Insecticides and herbicides are the most commonly used pesticides, and the spraying is carried out in the afternoon with a manual backpack sprayer. Although 95% of the producers read the package insert, they do not have adequate knowledge about pesticides toxicological classification. None of the producers uses the full personal protective equipment, and there are reports of malaise with the use of these products. Pesticides are stored in closed sheds together with agricultural implements, and 55% do not mix pesticides in the tank. The remainder of the products is used in another application, and the empty packagings are returned at resale. Spending on pesticides represents 1 to 5% of the production cost of vegetables that are sold in open markets and grocery stores. It is concluded that, due to the intermediate awareness level, vegetable producers need to be better oriented and assisted regarding the use of pesticides, through actions aimed at safety and technical instruction, to avoid future health problems and environmental issues.